2009
DOI: 10.1159/000231880
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Jaundice and/or a Lump in a Patient with Gall Bladder Cancer Mean that the Lesion Is Not Resectable?

Abstract: Background: The presence of jaundice or an abdominal lump in gall bladder cancer (GBC) is often translated to advanced and unresectable disease. We examined whether this was true. Methods: We retrospectively analysed 120 GBC patients, who had been operated on, for presenting symptoms, staging and resectability. The outcomes in patients with jaundice and/or an abdominal lump were compared with those who did not have these features. Early disease was represented by stages I and II, while stages III and IV repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
(16 reference statements)
2
11
0
Order By: Relevance
“…GBC has a female preponderance (about 75% globally) and the mean age of presentation in various reports is around 55 years [14,16,17,18]. In the present study, the mean age of GBC patients was 43.87 years with a male-to-female ratio of 1:2.25.…”
Section: Discussionsupporting
confidence: 49%
“…GBC has a female preponderance (about 75% globally) and the mean age of presentation in various reports is around 55 years [14,16,17,18]. In the present study, the mean age of GBC patients was 43.87 years with a male-to-female ratio of 1:2.25.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, in the same series (8)(9)(10)(11)(12), some jaundiced patients appeared to benefit from surgery in terms of survival following resection: with a mean 3-year survival of 20% and some real survivors at 3 and 5 years (8, 11), results never obtained in the subgroup of non-resected jaundiced patients. In the present series, overall survival was better in resected jaundiced patients than in non-resected jaundiced patients (p=.001) and the 3-year overall survival rates of 19% was comparable to the overall survival of resected patients with pancreatic adenocarcinoma in whom the principle of curative R0 resection has been established.…”
Section: Some Jaundiced Patients Appeared To Benefit From Surgerymentioning
confidence: 89%
“…In the light of these results, the authors concluded that "These data do not support routine operative exploration of patients with jaundice secondary to gallbladder cancer". However, several series experienced teams did not report such a poor outcome and showed that some jaundiced patients obtained improved survival following resection of GBC (8)(9)(10)(11)(12). A subgroup of jaundiced patients may therefore benefit from resection.…”
Section: Introductionmentioning
confidence: 99%
“…Even when patients with GBC presented with jaundice, the 5-year OS rate was 27%, and MST was 1.9 years, and some survived for 5 years. However, many reports describe that jaundice arising in patients with GBC indicates advanced disease and some believe that this precludes routine operative exploration [8,[15][16][17] . The difference between the present (4) 1 ( and these findings is that we achieved higher curative resection rates.…”
Section: Discussionmentioning
confidence: 99%